2022
DOI: 10.1037/tra0001087
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association between symptoms of posttraumatic stress and complicated grief: A random intercepts cross-lag analysis.

Abstract: Objective: Knowledge about the temporal relationship between disturbed grief and symptoms of posttraumatic stress disorder (PTSD) may have important implications for clinicians working with bereaved trauma survivors. We aimed to investigate the longitudinal association between symptoms of complicated grief and PTSD in a bereaved trauma-exposed sample. Method: In total, 275 bereaved survivors (M age = 19.3, SD = 4.6 years; 47.3% females) of the 2011 massacre on Utøya Island, Norway, participated in semistructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…PGD symptoms consistently preceded PTSD symptoms over the first 2 bereavement years (Fig. 2 ), consistent with three previous studies [ 19 , 20 , 22 ]. Separation distress [ 37 , 38 ] and stress sensitization theory [ 43 ], as described above, may similarly explain why PGD symptoms consistently predicted heightened PTSD symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…PGD symptoms consistently preceded PTSD symptoms over the first 2 bereavement years (Fig. 2 ), consistent with three previous studies [ 19 , 20 , 22 ]. Separation distress [ 37 , 38 ] and stress sensitization theory [ 43 ], as described above, may similarly explain why PGD symptoms consistently predicted heightened PTSD symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that symptoms of PTSD predicted subsequent PGD symptoms beyond the first bereavement year, consistent with the report for survivors of a terrorist attack [ 20 ]. A meta-analysis indicated the prevalence of PGD is much higher (49% [95% confidence interval (CI) 33.6, 65.4]) in people bereaved by unnatural or traumatic deaths [ 47 ] than by losses primarily due to diseases (9.8% [95% CI 6.8–14.0]) [ 48 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…r = .76; Boelen, van Denderen, & de Keijser, 2016 ), people exposed to disaster/terror attack (i.e. r = ≥ .79 ≤ .88 across four time-points; Lenferink et al, 2019 ; r = ≥ .57 ≤ .65 across three time-points; Glad, Stensland, Czajkowksi, Boelen, & Dyb, 2021 ), and internally displaced people (i.e. r = .50; Heeke, Stammel, & Knaevelsrud, 2015 ).…”
Section: Discussionmentioning
confidence: 99%